A new device for measuring ski running surface force and pressure profiles - Nilsson, J.; Karlöf, L.; Jakobsen, V. (Sports Engineering, 2013)
The pressure/force acting between the running surface of a ski and the snow may indirectly change glide friction. Thus, measuring the pressure/force distribution may be important for a deeper understanding of glide in skiing. The present aim was to construct a device that allowed the pressure/force underneath the ski running surface (SRS) to be recorded. Pressure sensors were attached on top of a platform. Sheets of different materials were used to improve the interaction between the SRS and the sensors. Possible functions of the device are demonstrated in three applications that emphasized comparison of force distribution underneath skis selected for similarity, force distribution under both skis and a single ski as well as backward weight distribution. The results show that the device with the pressure sensors mapped pressure/force distribution underneath the skis in the applications presented, and the system can thus be a useful tool for further optimizing e.g., ski designs.